The spirituality of rev. J.S. Mwale, minister of the Church of Central Africa, Presbyterian. Nkhoma Synod - Kamwana, Jonathan Johnstone Kasalika (Stellenbosch : Stellenbosch University, 2012)
Thesis (DTh)--Stellenbosch University, 1998.